Preoperative stereotactic radiosurgery in the management of brain metastases and gliomas - Lehrer, Eric J.; Kowalchuk, Roman O.; Ruiz-Garcia, Henry; Merrell, Kenneth W.; Brown, Paul D.; Palmer, Joshua D.; Burri, Stuart H.; Sheehan, Jason P.; Quninoes-Hinojosa, Alfredo; Trifiletti, Daniel M. (Frontiers in Surgery, 2022)
Stereotactic radiosurgery (SRS) is the delivery of a high dose ionizing radiation in a highly conformal manner while significantly sparing nearby healthy tissues. It is typically delivered in 1-5 sessions and has demonstrated safety and efficacy across multiple intracranial neoplasms and functional disorders. In the setting of brain metastases, postoperative and definitive SRS has demonstrated favorable rates of tumor control and improved cognitive preservation compared to conventional whole brain radiation therapy. However, the risk of local failure and treatment-related complications (e.g. radiation necrosis) markedly increases with larger postoperative treatment volumes. Additionally, the risk of leptomeningeal disease is significantly higher in patients treated with postoperative SRS. In the setting of high grade glioma, preclinical reports have suggested that preoperative SRS may enhance anti-tumor immunity as compared to postoperative radiotherapy. In addition to potentially permitting smaller target volumes, tissue analysis permits characterization of DNA repair pathways and tumor microenvironment changes in response to SRS, which may be used to further tailor therapy and identify novel therapeutic targets. Building on the work from preoperative SRS for brain metastases and preclinical work for high grade gliomas, further exploration of this treatment paradigm in the latter is warranted. Presently, there are prospective early phase clinical trials underway investigating the role of preoperative SRS in the management of high grade gliomas. In the forthcoming sections, we review the biologic rationale for preoperative SRS, as well as pertinent preclinical and clinical data, including ongoing and planned prospective clinical trials.